2014
DOI: 10.1093/schbul/sbt157
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Kynurenine Aminotransferase II in Psychiatric Diseases: Promising Effects of an Orally Active Enzyme Inhibitor

Abstract: Increased brain levels of the tryptophan metabolite kynurenic acid (KYNA) have been linked to cognitive dysfunctions in schizophrenia and other psychiatric diseases. In the rat, local inhibition of kynurenine aminotransferase II (KAT II), the enzyme responsible for the neosynthesis of readily mobilizable KYNA in the brain, leads to a prompt reduction in extracellular KYNA levels, and secondarily induces an increase in extracellular glutamate, dopamine, and acetylcholine levels in several brain areas. Using mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 48 publications
4
69
0
Order By: Relevance
“…Kynurenic acid, in turn, acts as an antagonist of NMDA receptors, creating a hypoglutamatergic state with decreased brain-derived neurotrophic factor (BDNF) and ultimately potentiating the dopaminergic hyperfunction in the limbic system that is responsible for the development of positive symptoms characteristic of SZ. 15,[58][59][60] In our study, we found that positive symptoms appear to be most robustly linked to inflammation, with more severe symptomatology correlated to higher levels of CRP. Thus, a pro-inflammatory state with activation of the kynurenine pathway may be one possible explanation for the association of CRP with SZ.…”
Section: Discussionsupporting
confidence: 52%
“…Kynurenic acid, in turn, acts as an antagonist of NMDA receptors, creating a hypoglutamatergic state with decreased brain-derived neurotrophic factor (BDNF) and ultimately potentiating the dopaminergic hyperfunction in the limbic system that is responsible for the development of positive symptoms characteristic of SZ. 15,[58][59][60] In our study, we found that positive symptoms appear to be most robustly linked to inflammation, with more severe symptomatology correlated to higher levels of CRP. Thus, a pro-inflammatory state with activation of the kynurenine pathway may be one possible explanation for the association of CRP with SZ.…”
Section: Discussionsupporting
confidence: 52%
“…A possible explanation is that KAT I (despite the name) may not be a major source of kynurenate in the brain. Indeed, it appears that workers in the field have recently emphasized the importance of KAT II as the major source of kynurenate in the brain (Potter et al 2010;Sathyasaikumar et al 2011;Wu et al 2014). Nevertheless, there is some evidence that KAT I/ GTK may have a neuroprotective role.…”
Section: Glutamine Transaminases and Cysteine S-conjugate β-Lyasesmentioning
confidence: 99%
“…As ɑ7nACh and NMDA receptors, which likely serve as preferential targets of KYNA in the mammalian brain in vivo (26, 27), are critical to neurogenesis and play central roles in modulating neuronal migration and integration during brain maturation (7276), we suspect that prolonged inhibition of these receptors, particularly during developmental periods, may be causally related to the behavioral phenotypes seen in adult Kmo −/− mice. Using biochemical, electrophysiological and behavioral outcome measures, experiments currently in progress in our laboratories are designed, inter alia , to investigate the impact of prenatal insults in both Kmo −/− and heterozygous ( Kmo +/− ) animals (77) and to evaluate genetic and pharmacological approaches to experimentally down-regulate brain KYNA levels in Kmo −/− mice (78, 79). However, caution is indicated when extrapolating studies with knock-out mice to pathological conditions in humans (80) and when assuming direct correlations between central and peripheral measures of KP metabolism (19).…”
Section: Discussionmentioning
confidence: 99%